Examination of the Attitudes of Students Studying in the Department of Special Education Teaching towards Childhood Epilepsies - Haylı, Çiğdem Müge; Chung, Seockhoon; Karataş, Ramazan; Demir Kösem, Dilek; Karay, Özlem (PT Inovasi Pratama Internasional, 2024)
It was conducted as a descriptive study to examine the attitudes of students studying in the special education teaching department towards childhood epilepsy. This research is descriptive and descriptive in nature. The data required for the research was collected between 01 June 2024 and 31 July 2024. The study group consisted of 328 students studying in special education teaching. Sociodemographic and Epilepsy Questionnaire data collection form and Social Attitudes Towards Childhood Epilepsy Scale (SATCES) were used with the online survey method in nurses working in the students studying in the special education teaching department by convenience sampling method from non-probability sampling methods who voluntarily participated in the collection of research data and filled out the informed consent form. SPSS 26.0 data analysis program was used in analysis of the data was carried out by sample t-test and ANOVA independent of paramedic statistical tecniques. It was determined that 71.1% of the participants were female and 24.1% were male. 52.4% of them were students of special education teaching department. A large proportion of the participants (47.3%) were second year students. According to the mean scores obtained, the attitudes of the students studying in special education teaching towards childhood epilepsy were found to be high and significant. It was found that there were significant differences between the attitudes of the students studying in special education teacher education towards childhood epilepsy and other sociodemographic descriptive information except for the variable in the age group (p<0.05). It was concluded that the attitudes of students studying in the special education teaching department towards childhood epilepsy differed significantly when examined in terms of certain socio-demographic variables. It can be suggested that students studying in special education teaching should be required to conduct academic studies to raise social awareness about children with epilepsy.